Vous êtes sur la page 1sur 3

a b c

a + 0 = a

a + S(b) = S(a + b)

a + b = b + a

a + (b + c) = (a + b) + c

a + b = a + c

b = c a + b = c + b a = c

a a + b

a b a = S(b)

a + b = 0 a = b = 0

a b c

a a

a b b c a c

a b b a a = b

a < b

a

b a + c b + c S(a) b

a < b c a + c = b a < b a = b a > b

m 0 P (m) m m 0

P (m ) m m 0 m < m

P (m) P (m) m

a b c

ab = ba

ab a b a(b + c) = ab + ac (a + b)c = ac + bc

(ab)c = a(bc)

ac = bc c a = b ab = ac a b = c

1 · a = a

ab = 0 a = 0 b = 0

a < b c ac < bc

a b b q

r a = bq + r 0 r < b

A B C X

A B = B A A B = B A

 

(A B) C

= A (B C) (A B) C = A (B C)

 

A ∪ ∅ = A

A ∩ ∅ =

A X = X A X = A

 

A A = A A = A

A (B

C)

= (A B) (A C) A (B C) = (A B) (A C)

A (X

\ A)

= X A (X \ A) =

X \ (A B) = (X \ A) (X

\ B) X

\ (A B) = (X

\ A) (X \ B)

A B

 

A B A B A B

= A = B

A B

A

A B B

C A C B C A B

A A B B A B

A C

B C A B C

A (A B) = A (A B) =

A

(a, b) (a, b) := {{a}, {a, b}} (a, b) = (c, d) a = c b = d

f : A B g : B C

g f : A C f g g f : A C g f

f : A B f g : B A

g f = A

f : A B f g : B A

f g = B

f

:

X

Y

X i X

f ( i X i ) =

f 1 ( i Y i ) =

i f(X i )

f ( i X i )

f 1 ( i Y i ) =

i f(X i ) i f(Y i ) i f(Y i )

Y j

Y

|A × B| = |B × A| A B

A = {1, 2, 3, 4} A × A

{(1, 1), (2, 2), (3, 3), (4, 4), (1, 2), (2, 1), (3, 4), (4, 3)}

{(1, 1), (2, 2), (3, 3), (4, 4), (1, 2), (1, 3), (1, 4), (2, 3), (2, 4), (3, 4)}

{(1, 1), (2, 2), (3, 3), (4, 4), (1, 2), (3, 4)}

{(1, 1), (2, 2), (3, 3), (4, 4), (1, 2), (2, 3), (3, 4)}

A × A

A = Z aRb

a | b

 

A = N aRb

a | b

A = Z aRb

a | b b | a

A

=

Z × (Z \ {0}) (a, b)R(c, d)

ad = bc

A = R 2 \ { 0} uRv v = αu α Q

¯

A = R 2 \ { 0} uRv v = αu α Z

¯

A = Z aRb

4 | a b

A R, Q A × A

R Q R Q R Q R Q

R A × A Q A × A aQb aRb bRa Q